Strategi Pembelajaran Menggunakan Metaverse Bagi Guru Di Madrasah Aliyah Al Hidayah - Indrabayu Indrabayu; Zahir Zainuddin; Ingrid Nurtanio; Amil Ahmad Ilham; Muhammad Niswar; Adnan Adnan; Elly Warni; Zulkifli Tahir; Ady Wahyudi Paundu; Christoforus Yohanes; Mukarramah Yusuf; A.Ais Prayogi; Anugrayani Bustamin; Iqra Aswad; Muhammad Alief Fadhal Imran Oemar; Intan Sari Areni; Zaenab Muslimin; Rieka Zalzabillah Putri; Aulia Darnilasari (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2022)
The rapid development of digital technology makes the world of education must continue to be dynamic and develop in order to produce adaptive and competent generations. Previously in conventional teaching methods, the material was taught by the teacher to students in the classroom orally or by telling students to read books to watch videos. However, with the online school method in Metaverse, it is hoped that it can provide clear explanations regarding material that is difficult to explain through books or videos. Metaverse is a future technology in the form of a virtual space where people from all over the world can gather and communicate using virtual technology. With the presence of a virtual world like this Metaverse, the world of education will be greatly helped. For example, when learning takes place, students can see firsthand how the machine works without having to cut it, the anatomy of the body without having to cut live animals or visiting a historical place without having to flock to ride buses all the way to the place they want to go, see phenomena and direct natural disasters, or even school buildings can also be built majestically in the Metaverse world. There are so many conveniences that we find when we use the Metaverse as a learning innovation in the future. Community service carried out at Madrasah Aliyah Al Hidayah, aims to provide insight into educational applications that will be used in the Metaverse so as to facilitate interaction between teachers at MA Al Hidayah and students, as well as provide enormous opportunities, especially for matters related to the world of education. , internet design and gaming. This community service is also a place to socialize research results at the Department of Informatics Engineering, namely Metaverse in the field of education. The results of the service showed that the level of understanding of the training participants increased significantly on the importance of Metaverse education.